Impact of Essential Nutrient Deficiency on the Growth and Yield of Four Hydroponic Vegetable Crops Using a Split-Plot Design in Hydroponic Systems (Applied Plant Physiology Study) - Abd. Hadid; Rois; Abdul Rahman; Chitra Angriani Salingkat; Jusriadi; Mustakim; Mustamin; Made Aditiya Dharma; Ni Ketut Dewi Kusuma Arsani (Postgraduate, University of Mataram, 2026)
Essential nutrients play critical roles in plant physiology; therefore, nutrient imbalance in hydroponics can rapidly reduce growth and yield. This study evaluated the effects of N, P, and K deficiencies on four hydroponic vegetable crops using a split-plot design to support nutrient-deficiency diagnosis and practical nutrient management. This study used a split-plot design, with four nutrient types as main plots: N0 (balanced N, P, K), N1 (nitrogen deficiency), N2 (phosphorus deficiency), and N3 (potassium deficiency). The second factor consisted of four types of vegetable crops as subplots: S1 (Pakcoy), S2 (Caisim mustard), S3 (Green Romaine), and S4 (Kangkung), resulting in 16 treatment combinations, each repeated four times, for a total of 64 experimental units. The results indicate that deficiencies in nitrogen (N), phosphorus (P), and potassium (K) significantly affect growth and yield in hydroponic systems. Across crops, N deficiency most consistently reduced vegetative growth and fresh weight, P deficiency primarily constrained root-related traits and leaf expansion, and K deficiency affected yield-related performance and quality attributes.